1978
DOI: 10.1007/bf01273259
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic observations on a ganglioneuroma

Abstract: This report describes some additional morphologic observations on a mediastinal ganglioneuroma. The neoplastic neurons contained argentaffin cytoplasmic granules presumably representing neurosecretory granules. Cytoplasmic inclusions resembling Pick's bodies were frequently observed in the neuronal components of the tumor. These inclusions consisted of neurofilaments mixed with a variable number of microtubules, dense core vesicles and other organelles. These findings expand the range of conditions in which Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 10 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Similar filamentous inclusions have been reported in aged DRGN of Wistar rats (Koistinaho et al, 1991), in developing human DRGN treated with intracellular tangles seen in ganglioneuromas (Bender and Ghatak, 1978).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similar filamentous inclusions have been reported in aged DRGN of Wistar rats (Koistinaho et al, 1991), in developing human DRGN treated with intracellular tangles seen in ganglioneuromas (Bender and Ghatak, 1978).…”
Section: Discussionmentioning
confidence: 71%
“…X 6,000 (A), X 4,800 (B), and X 21,600 (C,D). intracellular tangles seen in ganglioneuromas (Bender and Ghatak, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Although well differentiated, the ganglion cells vary in size, often being multinucleate, and contain Nissl substance in varying quantity; axons and Schwann sheaths are often bundled in pseudofascicles. Cytoplasmic vacuoles, inclusions, and even features of neurodegenerative change such as Pick bodies maybe seen [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the primitive nature of this tumor, however, its exact histogenesis and differentiating potential have been debated and have been extensively reviewed. 3,5,36 Although some authors have suggested the existence of neuroblastic differentiation in some medulloblastomas based on light microscopic 25,36,40,4 l ,4.5. 46 definitive evidence of neuronal differentiation has rarely been documented ultrastructurally.'"…”
mentioning
confidence: 99%